Basically, to solve this, we need to use the equation:
x^2 + 6x + 8 = 0
Now, to do this we need to simplify:
(x + 4)(x + 2) = 0
(When you multiply these two, you get x^2 + 6x + 8, you can check)
To make 0, one of these two have to make 0. In this case, one could be -4, and one could be -2
So, x = -4, and x = -2 (-2 is larger, -4 is smaller.)
Knowing this, we need to use -b/2a to find the vertex:
-6/2 = -3
Knowing that x is -3, we input it:
-9 + 18 - 8 = 1
Knowing this, we can say that the vertex is (-3, 1)